Pushing the envelope of physical vapor deposited thin-film based solid oxide fuel cells for 500 °C operation: Securing 1 W cm？2 performance, 1000 h stability, scale up to 15 W power, and associated limitations - Park, Jung Hoon; Oh, Seongkook; Yang, Byung Chan; Kim, Dong Hwan; Thieu, Cam-Anh; Hong, Jeeho; Park, Jeong Hwa; Lee, Jong-Ho; Yoon, Kyung Joong; Ji, Ho-Il; Lee, Kang Taek; Yang, Sungeun; et al. (Elsevier BV, 2025)
Thin-film solid oxide fuel cells (TF-SOFCs) open up new possibilities for SOFCs beyond their current reach by lowering the operating temperature. Here, we highlight key strategies to push the envelope of TF-SOFCs-scalability, performance, and stability-through the development of all cell components. Our innovations include using a conventional ceramic NiO-YSZ anode support modified with a physical vapor deposited anode functional layer, enabling reliable and scalable gas-impermeable thin-film electrolytes. To achieve a state-of-the-art performance of 1 W cm(-2) at 500 degrees C, we optimized each cell component: reducing anode particle size and introducing a mixed ionic and electronic conductor; enhancing cathode performance via deposition optimization of La0.6Sr0.4CoO3; and decreasing electrolyte ohmic resistance with a tri-layer GDC-YSZ-GDC structure using minimal thickness of YSZ. Long-term stability tests, >500 h, revealed that Ni protrusion through the electrolyte is the key degradation mechanism in TF-SOFCs. By lowering the Ni content in the anode, we achieved 1000 h durability with a degradation rate of 2.9 % kh(-1). Furthermore, we scaled up the cell to 5 x 5 cm(2) without compromising performance and achieved >15 W total power per cell at 500 degrees C, demonstrating practical applicability of TF-SOFCs. These strategies advance TF-SOFC technology and provide key insights into developing low-temperature SOFCs with improved scalability, performance, and stability.